Leaf Size Indices and Outline-Based Geomorphometric Analysis of Five Philippine Endemic Saurauia Willd. (Actinidiaceae) - Mazo, Kean Roe Felipe; Aribal, Lowell Gazo (Jurnal Sylva Lestari, 2025)
Species discrimination among species of Saurauia is challenging due to large morphological variation. This study examines the intraspecific variations of the 5 Philippine endemic Saurauia species using leaf size indices (LSI) and outline-based geometric morphometrics to facilitate species discrimination. Leaf samples were measured using the traditional method, scanned, converted to binary images, subjected to elliptic Fourier Analyses, and quantitatively analyzed using principal component analysis (PCA). The leaf morphology significantly differed among species based on the results of LSI and leaf shape outline analyses. The results showed 7 effective principal components (PCs), which accounted for 94.16% of the total variation. Significant differences were observed in all PCs. Discriminant analysis of the leaf shape outline confirmed the delimitation of species with scores relatively higher than the cut-off value. The tree topology from leaf shape outline, and leaf size indices all exhibited similarity in the clustering at the species level. A key to the species based on leaf morphology is also provided. Keywords: elliptic fourier analysis, kiwi, leaf size index, leaf variation, principal component analysis